Can Sex Competition Be Considered a Sport? - Sabater-Sala, Ana I.; Álvarez-Dardet, Carlos; Marcos-Marcos, Jorge (Archives of Sexual Behavior, 2025)
The article explores whether sex competition can be considered a sport activity, in reference to the Swedish Sex Federation's (SSF) holding of a sex championship. Topics discussed include studies examining the effects of sexual activity on sport activity or vice versa, gender differences with regards to performance in sports and different physical activities, and sections to evaluate in the SSF competition including seduction, oral sex and artistic execution of individual poses.